HUBUNGAN SINDROM METABOLIK DENGAN KEJADIAN OSTEOARTRITIS LUTUT PADA PASIEN OSTEOARTRITIS DI RSPAD GATOT SOEBROTO PERIODE 2015 - 2017 - Arinindya Putri Eka Lestari, - (2018)
Osteoarthritis (OA) of the knee is one of the most common joint disease found in Indonesia. One of the risk factor of the knee osteoarthritis at age 45-65 years is metabolic syndrome. The aim of this study is to determine whether metabolic syndrome relates to knee osteoarthritis incidence on osteoarthritis patients in Gatot Soebroto Central Army Hospital Period 2015-2017. This analytic observational study uses cross sectional approach. Sampling technique in this research was simple random sampling. The data of this research was obtained from medical record data of patients who have been diagnosed with osteoarthritis in Gatot Soebroto Central Army Hospital. From the total 190 subjects that are diagnosed with osteoarthritis that have the age group of 45-65 years old, 48,4% of them suffer from knee OA with the presence of metabolic syndrome, while 6,3% of the total subjects suffer from the other types of OA with metabolic syndrome. The result of bivariate analysis with Chi-Square shows that there's an association between metabolic syndrome and knee OA (p=0,032). The analysis shows that respondents with metabolic syndrome have a higher risk of knee osteoarthritis. Metabolic syndrome become one of the risk factors that will increase the occurrence of knee OA. The routine examination and the right management for metabolic syndrome as the risk factor of knee OA will decrease the incidence and the progressivity of knee OA.